THE EFFECT OF LEVERAGE ON TAX AVOIDANCE WITH INDEPENDENT COMMISSIONERS AND INSTITUTIONAL OWNERSHIP AS MODERATING VARIABLES - Oktaviani, Rachmawati Meita; Zulaikha, Zulaikha (The journal of contemporary issues in business and government, 2021)
This study aims to examine the effect of leverage on tax avoidance with independent commissioners and institutional ownership as moderating variables. The population in this study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) 2016-2020. This study uses secondary data. The sample of this study consisted of 15 companies the sampling technique used purposive sampling. The data were analyzed using the panel data moderation regression analysis method. The results show that leverage has no and significant effect on tax avoidance, independent commissioners can weaken the effect of leverage on tax avoidance, and institutional ownership does not moderate the effect of leverage on tax avoidance.